Data collection in pandemic times: the case of the Belgian COVID-19 health surveys - Elise Braekman; Rana Charafeddine; Finaba Berete; Helena Bruggeman; Sabine Drieskens; Lydia Gisle; Lize Hermans; Johan Van der Heyden; Stefaan Demarest (BMC, 2023)
Abstract Background Survey data were needed to assess the mental and social health, health related behaviors and compliance with preventive measures of the population during the COVID-19 pandemic. Yet, the pandemic challenged classical survey methods. Time and budgetary constraints at the beginning of the pandemic led to ad hoc recruitment of participants and easily manageable data collection modes. This paper describes the methodological choices and results in terms of participation for the COVID-19 health surveys conducted in Belgium. Methods The COVID-19 health surveys refer to a series of ten non-probability web surveys organized between April 2020 and March 2022. The applied recruitment strategies were diverse including, amongst others, a launch through the website and the social media of the organizing research institute. In addition, the survey links were shared in articles published in the national press and participants were requested to share the surveys in their network. Furthermore, participants were asked consent to be re-contacted for next survey editions using e-mail invitations. Results These mixed approaches allowed to reach a substantial number of participants per edition ranging from 49339 in survey 1 to 13882 in survey 10. In addition, a longitudinal component was created; a large share of the same individuals were followed up over time; 12599 participants completed at least 5 surveys. There were, however, sex, age, educational level and regional differences in participation. Post-stratification weighting on socio-demographic factors was applied to at least partly take this into account. Conclusion The COVID-19 health surveys allowed rapid data collection after the onset of the pandemic. Data from these non-probability web surveys had their limitations in terms of representativeness due to self-selection but were an important information source as there were few alternatives. Moreover, by following-up the same individuals over time it was possible to study the effect of the different crisis phases on, amongst others, the mental health. It is important to draw lessons from these experiences: initiatives in order to create a survey infrastructure better equipped for future crises are needed.